2021
DOI: 10.3389/fmats.2021.651957
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed Epitaxial Growth of MAPbI3 Single-Crystal Films for Highly Stable Photodetectors

Abstract: Recent years, organic-inorganic hybrid perovskites (OIHPs) have been widely used in applications, such as solar cells, lasers, light-emission diodes, and photodetectors due to their outstanding optoelectronic properties. Nowadays photodetectors based on perovskite films (PFs) suffer from surface and interface traps, which result from low crystalline quality of perovskite films and lattice mismatch between perovskite films and substrates. Herein, we fabricate MAPbI3 -(MA = CH3NH3) single-crystal films (SCFs) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…In this study, n -MAPbBr 3 served as the substrate and the MAPbI 3– x Br x and MAPbI 3 epitaxial layers were grown on the opposite sides of the substrate. As previously reported, the MAPbI 3 epitaxial layer on the MAPbBr 3 PSC exhibited excellent optoelectrical performance . Scanning electron microscopy (SEM) images and energy-dispersive X-ray spectroscopy (EDX) mappings of the cross section of our dual-mode PD revealed that the Br – ions were incorporated into the MAPbI 3– x Br x perovskite lattice (Figure d).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…In this study, n -MAPbBr 3 served as the substrate and the MAPbI 3– x Br x and MAPbI 3 epitaxial layers were grown on the opposite sides of the substrate. As previously reported, the MAPbI 3 epitaxial layer on the MAPbBr 3 PSC exhibited excellent optoelectrical performance . Scanning electron microscopy (SEM) images and energy-dispersive X-ray spectroscopy (EDX) mappings of the cross section of our dual-mode PD revealed that the Br – ions were incorporated into the MAPbI 3– x Br x perovskite lattice (Figure d).…”
Section: Resultssupporting
confidence: 75%
“…As previously reported, the MAPbI 3 epitaxial layer on the MAPbBr 3 PSC exhibited excellent optoelectrical performance. 28 Scanning electron microscopy (SEM) images and energy-dispersive X-ray spectroscopy (EDX) mappings of the cross section of our dual-mode PD revealed that the Br − ions were incorporated into the MAPbI 3−x Br x perovskite lattice (Figure 1d). To evaluate the doping ratio of Br − in MAPbI 3−x Br x epitaxial layer and Bi 3+ in the n-MAPbBr 3 substrate, EDX was conducted as displayed in Figure S2.…”
Section: Resultsmentioning
confidence: 96%
“…The samples used in this work are MAPbI 3 polycrystalline grains and thin films. Firstly, high-quality MAPbI 3 single-crystals were synthesized according to the literature [60][61][62] . The photographs of the MAPbI 3 single crystal and the corresponding X-ray diffraction (XRD) pattern are given in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The lattice match rate is sufficient to achieve epitaxial growth. [34][35][36][37][38] In the fabrication process of hetero-PD, high-quality (doped MAPbCl 3 ) PSCs are used as substrates, as shown in Figure 1c. Intrinsic MAPbBr 2.5 Cl 0.5 and doped MAPbBr 3 were epitaxially grown on the substrates.…”
Section: Resultsmentioning
confidence: 99%